Evaluation of a Micro CT scan system based on digital image correlation profile - Alfieta Rohmaful Aeni; Gede Bayu Suparta (Universitas 'Aisyiyah Yogyakarta, 2021)
The centre of rotation position is a factor that needs to be controlled to avoid artefact in CT scan. A method to evaluate the performance of CT system is needed. The method is developed using x-ray micro-CT system and evaluated based on Digital Image Correlation (DIC). The method of this research is experiment. The multiple radiographs are obtained from scanning object by simulation and experiment. The results show that the ideal DIC profile value of radiograph image from simulation is a constant straight line for every size variation of the object. However, from the experiment, the result show deviation toward –y for every size variation of the object that indicate the shift of COR position in micro-CT system. The result also similar using centre of mass profile value as comparison.